Synthesis of titanium dioxide microspheres via a modified hydrothermal method utilizing schott bottle and improvised clamp - Musa, Mohamed Zahidi; A. Subki, A. Shamsul Rahimi; Malek, Mohd Firdaus; Parimon, Norfarariyanti; Mamat, Mohamad Hafiz (Malaysian Institute of Chemistry, 2025)
A synthesis of titanium dioxide (TiO2) microspheres has been realized via a facile hydrothermal method utilizing glass bottle and stainless-steel clamp. The unique structure has been produced after 4 hours of deposition time at the temperature of 150°C. The resulting samples were analysed using FESEM, XRD, Raman spectroscopy, XPS, and humidity sensing measurement. FESEM images revealed the TiO2 microspheres shape with the average diameter of 5 µm, are constructed of smaller dendritic TiO2 nanorods. XRD analysis confirmed that the TiO2 is of a rutile structure with preferred orientation at (110), and (101) plane. Raman vibration mode was detected at 143 cm-1, 235 cm-1, 447 cm-1, and 612 cm-1, which correspond to B1g and two-phonon bands Eg and A1g, respectively. It is expected that the projected ultra-high surface area of the structure can be advantageous for various applications.